Alteration of gate-oxide trap capture/emission time constants by channel hot-carrier effect in the metal-oxide-semiconductor field-effect transistor - Ju, Xin (2021)
Electrical-stress-invariant gate-oxide traps' capture and emission time constants have been the basis of aging models as well as applications that leverage the stochastic nature of the capture and emission processes, such as the true random number generator. In this work, we show that this presumption is only valid for about two-thirds of the oxide-trap population studied. For the remaining one-third, the traps' capture and/or emission time constants could be changed by the channel hot-carrier (CHC) effect. Such a behavior is found in both polysilicon/silicon oxynitride gated and TiN/HfO2 gated transistors. A reversion of the altered trap time constant to the value before the CHC-stress is also observed, but the period varies significantly for different traps (from several hours to months). Since the CHC stress effect is present in all scaled transistors, the findings would have important implications for models/applications that presume oxide-trap properties to be stress-invariant.